2008
DOI: 10.1097/01.aoa.0000326377.81874.02
|View full text |Cite
|
Sign up to set email alerts
|

Cell Salvage in Obstetrics

Abstract: thrombophilia, antenatal and postpartum prophylaxis should be used. Prophylactic treatment with LMWH or UFH can be stopped at 12 to 24 hours before induction or elective CS; full anticoagulation should be withheld for 24 hours.For asymptomatic women with no prior VTE or APO but with thrombophilia, there is not enough evidence to recommend anticoagulant drug treatment during pregnancy, unless there are other risk factors. Those with AT-III deficiency, or who are homozygotes, or compound heterozygotes for factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…52 To minimise transfusion requirements, several institutions use cell salvage at the time of peripartum hysterectomy. [53][54][55][56][57] Although cell salvage could theoretically reinfuse fetal debris and possible result in alloimmunisation, several studies in obstetrics have demonstrated the safety of the technology. [53][54][55][56][57] The last two decades have also seen the introduction of a number of pro-haemostatic agents to assist with the control of operative bleeding.…”
Section: Perioperative Considerationsmentioning
confidence: 99%
“…52 To minimise transfusion requirements, several institutions use cell salvage at the time of peripartum hysterectomy. [53][54][55][56][57] Although cell salvage could theoretically reinfuse fetal debris and possible result in alloimmunisation, several studies in obstetrics have demonstrated the safety of the technology. [53][54][55][56][57] The last two decades have also seen the introduction of a number of pro-haemostatic agents to assist with the control of operative bleeding.…”
Section: Perioperative Considerationsmentioning
confidence: 99%
“…Our study was based on the premise that involvement of ICSA in the development of AFE can be evaluated by comparing changes in AFE‐related markers in mothers who have undergone cesarean sections with and without ICSA. The pathogenesis of AFE remains unclear, but fetal components in the amniotic fluid that flow into the maternal blood are a primary trigger 19 . Once AFE develops, the anaphylactoid reaction overactivates the complement and coagulation fibrinolytic systems, resulting in DIC and atonic bleeding 20–22 .…”
Section: Discussionmentioning
confidence: 99%
“…Although common in the nonpregnant trauma population, the current trend toward early replacement of coagulation factors and platelets has not been studied in pregnant trauma patients but seems reasonable in the setting of massive hemorrhage. In an effort to reduce transfusion requirements, cell salvage has become more popular in surgical cases; there is increasing evidence that cell salvage is safe in obstetric patients, but the practice remains controversial (Allam et al 2008).…”
Section: Circulationmentioning
confidence: 99%